Comprehensive study of altered proteomic landscape in proximal renal tubular epithelial cells in response to calcium oxalate monohydrate crystals - Zhu Wang; Ming-xing Li; Chang-zhi Xu; Ying Zhang; Qiong Deng; Rui Sun; Qi-yi Hu; Sheng-ping Zhang; Jian-wen Zhang; Hui Liang (BMC Urology, 2020)
Abstract Background Calcium oxalate monohydrate (COM), the major crystalline composition of most kidney stones, induces inflammatory infiltration and injures in renal tubular cells. However, the mechanism of COM-induced toxic effects in renal tubular cells remain ambiguous. The present study aimed to investigate the potential changes in proteomic landscape of proximal renal tubular cells in response to the stimulation of COM crystals. Methods Clinical kidney stone samples were collected and characterized by a stone component analyzer. Three COM-enriched samples were applied to treat human proximal tubular epithelial cells HK-2. The proteomic landscape of COM-crystal treated HK-2 cells was screened by TMT-labeled quantitative proteomics analysis. The differentially expressed proteins (DEPs) were identified by pair-wise analysis. Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of DEPs were performed. Protein interaction networks were identified by STRING database. Results The data of TMT-labeled quantitative proteomic analysis showed that a total of 1141 proteins were differentially expressed in HK-2 cells, of which 699 were up-regulated and 442 were down-regulated. Functional characterization by KEGG, along with GO enrichments, suggests that the DEPs are mainly involved in cellular components and cellular processes, including regulation of actin cytoskeleton, tight junction and focal adhesion. 3 high-degree hub nodes, CFL1, ACTN and MYH9 were identified by STRING analysis. Conclusion These results suggested that calcium oxalate crystal has a significant effect on protein expression profile in human proximal renal tubular epithelial cells.